Exploring the Construct of Psychological Safety in Medical Education. (30th July 2019) - Tsuei, Sian Hsiang-Te; Lee, Dongho; Ho, Charles; Regehr, Glenn; Nimmon, Laura
Abstract : Purpose: Psychological safety (PS) is recognized as key in health professional education. However, most studies exploring PS in medical education have focused on mistreatment, thus focusing on what PS is not . The authors set out to explicitly explore learners' concept of PS in the context of medical education to better understand and define PS and its educational consequences for medical students. Method: This descriptive exploratory study was conducted in the context of a pilot peer-assisted learning (PAL) program. The program brought together residents and medical students for 16 semi-formal learning sessions. Eight medical students from a PAL program were recruited for semi-structured interviews to explore their experiences of PS. Transcripts were thematically analyzed using an inductive approach, and social ecological theory was integrated in the latter stages of analysis. Results: Students described PS as not feeling judged. Having supportive relationships with peers and mentors improved PS. Students' sense of PS appeared to free them to focus on learning in the present moment without considering the consequences for their image in the eyes of others. Feeling safe also seemed to facilitate relationship building with the mentors. Conclusions: A sense of PS appears to free learners from constantly being self-conscious about projecting an image of competence. This enables learners to be present in the moment and concentrate on engaging with the learning task at hand. The authors propose the term "educational safety" be used to describe a relational construct that can capture the essence of what constitutes psychological safety for learners.